Testing of mathematical knowledges and skills of the first course students of Vilnius Gediminas technical university - Krylovas, Aleksandras; Raulynaitis, Juozas (Lietuvos matematikos rinkinys, 2005)
The research of the methods for testing of mathematical knowledges and skills of the universitety students is presented. The article continues previous works of the authors.